Three stages of entrepreneurial orientation: the founder's role. Issue 2 (8th November 2019) - Ljungkvist, Torbjörn; Boers, Börje; Samuelsson, Joachim
Abstract : Purpose: The purpose of this paper is to understand the development of the five dimensions of entrepreneurial orientation (EO) over time by taking a founder's perspective. Design/methodology/approach: The paper draws on an in-depth single-case study. It combines semi-structured interviews in the company with archival data, such as annual reports, press clips and interviews in business magazines. Findings: The results indicate that the EO dimensions change from being personalized and directly solution-oriented to being intangible value-creation-oriented. Originality/value: By suggesting ownership-based EO configurations, this study contributes insights into how different ownership forms propel EO. These configurations – that is, personal, administrative based and intangible focused – show the impact of the EO dimensions and provide a systematic and theoretical understanding of EO change over time.